VERTICAL DISTRIBUTION OF NUTRIENTS ON TRANSITIONAL SEASON IN WEDA BAY, NORTH MALUKU - Faisal Hamzah; Abdul Basit; Iis Triyulianti (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
A vertical distribution of nutrient shows an interaction of physical processes, source, and uptake along the water column. These interactions can occur along the water column with different processes in each layer. Water samples from 17 stations were collected for nitrate, phosphate, and silicates concentration analyses during the transitional season in the Weda Bay. During the transitional season, the Weda Bay was characterized by low salinity (33.55-34.10), relatively warm temperature (30.87°C), and the relatively low nutrient concentrations (nitrate=0.03-4.87 µg at/l, phosphate=0.011-0.852 µg at/l, and silicate=0.04-1.21 µg at/l). The present of Western North Pacific Ocean (WNPO) watermass and the influence of Southern Subtropical Lower Water (SSLW) producing high salinity (>35) at the depth of 130-300 m were observed along the Weda Bay. Nutrient geochemical processes in this region were shown by nutrient utilization and regeneration across the water columns. Nutrients utilization was relatively high in the surface layer. Meanwhile, nutrients regeneration and remineralization were more dominant in the thermocline and deeper water layers. Analyses of nutrients showed that nitrate was more dominant than other nutrients with N/P ratio was 3.83-37.99 and N/Si ratio was 0.12-10.98. The effectiveness of silicate (0.25 μg at/l) that was used by phytoplankton found at a depth of 200 m when its concentration decreased at N/P ratio (16:08) close to the Redfield ratio. Due to an uptake, remineralization, and regeneration processes in each layer, a nutrient distribution pattern was formed which the nutrient concentrations decreased in mixed layer and increased in the deeper water.Keywords:nutrien, pattern, Weda Bay, transitional season